A Constructivist–Scientific Approach to AI Integration in Islamic Education in the Society 5.0 - Syifa Adilla Zahra; Sulastri Sulastri; Imam Syafe’i; Ahmad Fauzan; Sunarto Sunarto (Ahlussunnah: Journal of Islamic Education, 2026)
This study aims to analyze the integration of Artificial Intelligence in Islamic Religious Education learning through the perspectives of constructivist theory and the scientific approach in the Society 5.0 era. Islamic Religious Education learning is expected not only to develop the spiritual dimension but also to promote active, reflective, and contextual engagement of learners. Within this framework, constructivism positions learners as active subjects in constructing knowledge, while the scientific approach emphasizes a systematic learning process through the stages of observing, questioning, experimenting, reasoning, and communicating. This study employs a qualitative research method with a content analysis approach by examining scientific literature, educational regulations, and relevant learning theories. The findings reveal a gap between ideal expectations and the actual implementation of Artificial Intelligence in Islamic Religious Education learning, which is caused by limited digital competence among teachers, the absence of well-formulated ethical guidelines for the use of Artificial Intelligence, and the lack of learning models integrated with Islamic values. This study highlights the urgency of developing an Artificial Intelligence-based Islamic Religious Education learning model that is constructivist and scientific as a conceptual contribution to addressing educational challenges in the Society 5.0 era.